Karakterisasi dan Potensi Antibakteri Ekstrak Kapang Endofit Hasil Isolasi dari Sargassum sp.: Characterization and Antibacterial Potential of Endophytic Fungi Extracts Isolated from Sargassum sp. - Ridhwan, Muhammad; Radiastuti, Nani; Bahri, Saiful; Muhammad, Alfianur Azmi; Dwikencana, Windy; Haribowo, Dinda Rama; Solihat, Nur Amaliah; Ramadhan, Firdaus (Jurnal Sumberdaya Hayati, 2024)
The bioactive potential in Sargassum sp. and its direct use is expected to reduce its population in nature if used continuously. Using endophytic fungi from the host is a solution for obtaining bioactive compounds from Sargassum sp. The purpose of this study was to characterize endophytic fungi in Sargassum sp. and its potential as an antibacterial agent. Endophytic fungi were isolated using the direct planting technique, endophytic fungi were characterized through microscopic and macroscopic observations. Extraction was performed with two organic solvents, namely ethanol and ethyl acetate. Antibacterial potency was tested using the agar diffusion method using Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Salmonella typhi. Based on the results, two mold isolates, D3P1 and D4P1, were obtained. The ethyl acetate extract of D3P1 had the highest inhibition zone for Bacillus subtilis bacteria, with the highest inhibition zone being 23.2 mm for Bacillus subtilis and the smallest being 17 mm for Escherichia coli. The ethyl acetate extract of D3P1 had the highest inhibition zone compared to the ethyl acetate extract of D4P1 and the ethanol extract of D3P1 and D4P1. The GC-MS analysis identified four compounds that have been identified in the ethyl acetate extract of D3P1 isolates, among others, 2,3-Butanediol, Phthalic acid, 1,2-Benzenedicarbocylic acid, and 1-Anthracenamine. Phthalic acid and 1,2-Benzenedicarboxylic acid compounds have the potential as antibacterial.